2016
DOI: 10.1002/da.22505
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine for Treatment-Resistant Unipolar and Bipolar Major Depression: Critical Review and Implications for Clinical Practice

Abstract: There is an urgent need for more rapidly effective pharmacotherapies for major depressive disorder and bipolar disorder (BP) that are efficacious and tolerable for depressed patients who respond poorly to conventional treatments. Multiple controlled trials have now demonstrated a rapid, nonsustained antidepressive response to a single intravenous infusion of ketamine. Early controlled studies of intranasal or serial infusion therapy appear promising. The effective dose for depression is lower than the typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 95 publications
2
74
0
6
Order By: Relevance
“…Thus it is not known for how long the GBCr changes would last and whether repeated ketamine would have comparable effects. To the extent the observed GBCr changes are related to depression relief and to the ketamine-induced synaptogenesis, we speculate that GBCr changes could last for about 10 days; that is the approximate length of antidepressant response in humans (Bobo et al, 2016) and of the synaptogenic effects in rodents (Duman, 2014). Frequent daily administration of ketamine could lead to repeated glutamate surge, increased extracellular glutamate, excitotoxity, and synaptic dysconnectivity comparable to chronic stress models of depression (Abdallah et al, 2015), consistent with clinical data showing impaired cognition and depressive symptomatology in ketamine abusers (Fan et al, 2016;Morgan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is not known for how long the GBCr changes would last and whether repeated ketamine would have comparable effects. To the extent the observed GBCr changes are related to depression relief and to the ketamine-induced synaptogenesis, we speculate that GBCr changes could last for about 10 days; that is the approximate length of antidepressant response in humans (Bobo et al, 2016) and of the synaptogenic effects in rodents (Duman, 2014). Frequent daily administration of ketamine could lead to repeated glutamate surge, increased extracellular glutamate, excitotoxity, and synaptic dysconnectivity comparable to chronic stress models of depression (Abdallah et al, 2015), consistent with clinical data showing impaired cognition and depressive symptomatology in ketamine abusers (Fan et al, 2016;Morgan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An uncontrolled report has emerged of a synergistic effect between S-ketamine and ECT [56]. However, even if it prolongs seizure duration, ketamine has generally not been found to be effective in augmenting ECT [46, 49, 57], possibly because the rate of response to ECT is so high that it is difficult to augment it. In 1 or 2 doses, ketamine might be an appropriate choice for severely depressed and acutely suicidal patients while a more definitive rapidly acting treatment such as ECT is being arranged.…”
Section: What About Ketamine?mentioning
confidence: 99%
“…Ketamine is not FDA approved for depression, and its off-label use has become controversial because of its history as a substance of abuse. However, the use of ketamine in the treatment of severe depression continues to be an area of interest by many in the field of psychiatry due to the relatively limited number of treatment options for patients with severe treatment-resistant depression [1][2][3]7].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that electroconvulsive therapy reduced suicide in patients with the schizoaffective disorder [23]. Ketamine has been found helpful in both unipolar and bipolar depression [1][2][3]. In bipolar depression, Zarate at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation